Meningkatkan Kemampuan Berpikir Kritis Anak Usia Dini melalui Pembelajaran Sains Kontekstual di RA Al-Hidayah - Nurdiani, Silfi (AS-SABIQUN, 2024)
The capacity to assess arguments, examine data, and draw logical conclusions is known as critical thinking. Contextual learning is a technique to learning that works well for scientific education. The goal of the research was to enhance the critical thinking skills of young children at RA Al-Hidayah through contextual scientific instruction, as their critical thinking abilities are still poor. A classroom action research (PTK) design utilizing the Kemmis and McTaggart spiral model is employed in this study. Descriptive qualitative data analysis is the method employed. Group B is the early childhood research subjects. Ten kids served as the research subjects. Worksheets, interview instructions, and observation sheets were the equipment utilized in this study. The study's findings demonstrate how well this intervention works to help young children develop their critical thinking skills. According to this study, contextual scientific learning interventions have been shown to be successful in raising young children's critical thinking abilities across the board.